ANALISIS SEMIOTIK PADA PUISI “KARANGAN BUNGA” KARYA TAUFIK ISMAIL - Fitria Dwi Widiastuti (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2022)
Poetry is a literature that contains many building elements, one of which is the meaning of poetry, to analyze the meaning of a poem, a semiotic approach to poetry can be used. Semiotics has a meaning as a sign. The sign here can be a theme, value or meaning of a word or sentence in poetry. In this study, the researcher will analyze the poem entitled “Wreath of Flowers” ​​by Taufik Islamil using a semiotic approach, which is to tell the results of poetry analysis based on the data obtained. The research is based on the curiosity to know the meaning or value of the poem "Wreath of Flowers". The formulation of the malasah that will be studied is, how are the results of the semiotic analysis in Taufik Ismail's poem entitled "Wreath of Flowers"?. The goal is to find the meaning, theme or value contained in the poem "Wreath of Flowers". The results obtained in this semiotic analysis are, the poem "Wreath of Flowers" has the theme of struggle, passion or heroism, the moral values ​​are seen from the three small children who appreciate and respect the services of someone who sacrificed to fight for the welfare of the Indonesian people by giving a bouquet of flowers. the meaning of the poem contains feelings of sadness and grieving